PENGARUH NET PROFIT MARGIN (NPM) DAN DEBT TO EQUITY RATIO (DER) TERHADAP HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR KOSMETIK DAN RUMAH TANGGA - Nurlinda Nurlinda; Nurhayati Nurhayati (LP2M Universitas Bina Bangsa, 2023)
The cosmetics and household sub-sector companies are part of one of the consumer goods industry sectors listed on the IDX. This study aims to determine and analyze the effect of Net Profit Margin (NPM) and Debt To Equity Ratio (DER) on Cosmetic and Household Sub-Sector companies listed on the IDX. This type of research is associative using quantitative data types from secondary data sources. The research instrument is in the form of a list of tables in the form of financial statements containing total liabilities and total equity, an income statement consisting of net sales and net income, as well as a 2017-2021. The population used in this study were all cosmetics and household sub-sector companies listed on the IDX from 2017-2021 with a total of 10 companies. The samples in this study are 3 Cosmetics and Household Sub-Sectors listed on the Indonesian Stock Exchange from 2017-2021. The sampling technique used in this research is purposive sampling technique. Data collection techniques using library research and documentation. Data analysis techniques used the classical assumption test (consisting of the normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test), multiple linear analysis, coefficient and determination tests, and hypothesis testing using the t test, f test. The results of the study state that the Net Profit Margin (NPM) and the Debt-to-Equity Ratio (DER) together have a significant influence on stock prices